2019
DOI: 10.1001/jama.2018.16665
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G4 Levels

Abstract: A 67-year-old man with type 2 diabetes mellitus and hyperlipidemia was evaluated for unintentional weight loss of 28 lb (12.7 kg) and increasing fasting blood glucose values over the past 6 months. A computed tomography scan showed diffuse enlargement of the pancreas with peripheral hypoenhancement but no discrete mass. Soft tissue surrounded the infrarenal abdominal aorta, extended along the common iliac arteries, and obstructed the left ureter, causing hydronephrosis. He was referred for evaluation of possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…72 Some studies have suggested that IgG4-RD represents a premalignant state or a paraneoplastic condition. [155][156][157][158][159] For example, Wallace et al 160 reported that a history of malignancy is 2.5-fold more likely in patients with IgG4-RD compared with the general U.S. population. The presence of malignancies was associated with older age, higher serum IgG4 concentration; no cases of IgG4-RD involved the organ previously affected by cancer.…”
Section: Prognosis and Follow-upmentioning
confidence: 99%
“…72 Some studies have suggested that IgG4-RD represents a premalignant state or a paraneoplastic condition. [155][156][157][158][159] For example, Wallace et al 160 reported that a history of malignancy is 2.5-fold more likely in patients with IgG4-RD compared with the general U.S. population. The presence of malignancies was associated with older age, higher serum IgG4 concentration; no cases of IgG4-RD involved the organ previously affected by cancer.…”
Section: Prognosis and Follow-upmentioning
confidence: 99%
“…A diagnosis of AIP would require elevated IgG4 levels in addition to associated imaging features suggestive of AIP, which was not seen in this case. 10 Invasive procedures, such as fine-needle aspiration, have the potential to cause APdwith additional risks, including bleeding and infectiondand would be unlikely to change management.…”
mentioning
confidence: 99%